Khamr Criminal Act and Its Resolution in Subulussalam City, Aceh - Barutu, Ali Geno (Al-Risalah, 2019)
The enactment of khamr qanun in Aceh shows Aceh government’s commitment in prohibiting and eradicating khamr and similar drinks. However, the enforcement of the qanun has not been effective, especially in the City of Subulussalam as evidenced in several violations of the qanun. This paper aims to discuss what and how the khamr qanun in Subulussalam, its effectiveness, obstacles faced by the Subulussalam city government in enforcing the qanun, and solutions offered by the city government. After examining relevant literature and conducting observations, discussions, and interviews with Subulussalam City leaders, this paper concludes that the ineffectiveness of the khamr qanun enforcement is due to some constraints, such as lenient punishment, limited human resources, weak socialization of Islamic law and community education.